A randomised trial to compare the performance of Oxyzyme® and Iodozyme® with standard care in the treatment of patients with venous and mixed venous/arterial ulceration - Moffatt, Christine J.; Stanton, Julie; Murray, Susie; Doody, Veronica; Davis, Paul J.; Franks, Peter J. (Elsevier, 2014)
This study was to evaluate the potential benefits of two products (Oxyzyme® & Iodozyme®) into a leg ulcer service in South Staffordshire, UK. A randomised controlled Trial (RCT) was used to evaluate time to ulcer healing, quality of life, pain and cost effectiveness. 100 patients were randomised to receive either Oxyzyme/ Iodozyme (active group) or standard care (control group) with venous or mixed arterio-venous ulcers. Patients were evaluated weekly up to 12 weeks, with further follow up at 24 weeks. Whilst there was a small benefit in terms of healing over follow up using the Cox Proportional Hazards Model, this did not achieve a standard level of statistical significance (Hazard Ratio= 1.13, 95%CI 0.64 to 2.02, p=0.67) after adjustment for confounding factors. Patients with high protease activity showed an improved and faster healing in the active group, (HR=1.35, 95%CI 0.63, 2.87)p=0.44. The active group required significantly fewer dressing changes (14.8 versus 10.0, p=0.033). Despite the dressing costs being higher, there was a significantly lower cost of nursing time, leading to a greater cost effectiveness in terms of cost per healed ulcer (£977 versus £1071. A Markov model used to assess cost effectiveness in the main trial found that the control group had slightly better outcomes (12 more ulcer free weeks), but at a substantially greater cost (£5,031). When those with high protease activity the cost in the active group dominated, with lower cost (-£2,450) and an improved outcome (29 more ulcer free weeks). Health related quality of life (HRQoL) and pain significantly improved over the assessment period, though there was no difference between the treatment groups. The use of Oxyzyme® & Iodozyme®) could provide better value for money in the management of venous and mixed arterio-venous ulcers than standard care in a community leg ulcer service.